2016
DOI: 10.1016/j.eucr.2016.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Bladder Xanthoma – Is Immunohistochemistry Necessary?

Abstract: Urinary Bladder Xanthomas (UBX) are non-neoplastic reactive tumor like process. Isolated UBX is rare with only around 15 cases reported (Yu, Patel, & Bonert, 2015). UBX are reported in older patients who present with non specific symptoms like UTI or hematuria. Patients often have associated lipid anomalies. UBX have been vaguely described as yellowish white plaques or patches. Also, recent reports have stressed on the role of Immunohistochemistry in the diagnosis (Al-Daraji, Varghese, & Husain, 2007; Vimal, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Majority of the cases in the literature are ≥50 years old. The patient in our case was 38 years old, and as far as we know, he is the second youngest patient in the literature to be diagnosed with bladder xanthoma after a 34-year-old patient presented by Raghavendran et al 3 Xanthoma may be associated with bladder tumor or it can be found isolated. In the only series about this subject Yu et al evaluated 17 patients with bladder xanthoma and reported that xanthoma was usually associated with low grade urothelial cancer.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Majority of the cases in the literature are ≥50 years old. The patient in our case was 38 years old, and as far as we know, he is the second youngest patient in the literature to be diagnosed with bladder xanthoma after a 34-year-old patient presented by Raghavendran et al 3 Xanthoma may be associated with bladder tumor or it can be found isolated. In the only series about this subject Yu et al evaluated 17 patients with bladder xanthoma and reported that xanthoma was usually associated with low grade urothelial cancer.…”
Section: Discussionmentioning
confidence: 63%
“…Differential diagnosis includes xanthogranulomatous cystitis, malakoplakia, signet ring cell carcinoma and granular cell tumor. 2,3,9 In conclusion, xanthoma is a benign lesion which is very rarely found in the bladder. They are usually detected incidentally during cystoscopy.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…4 Foamy macrophages in the bladder can be found in other conditions such as malakoplakia, xanthogranulomatous cystitis, atypical mycobacterial infection, and signet ring carcinoma. 4 Immunohistochemistry staining for anti-CD68 has been demonstrated as a mainstay method for confirming foamy macrophages although the necessity of this to diagnose xanthoma has been questioned by Raghavendran et al 10 The management strategies are broad and include initial conservative management; however, in cases with uncontrollable bleeding or causing lower urinary tract symptoms, cystodiathermy, cold cup biopsy, transurethral resection, and partial cystectomy have been utilized. In terms of followup, as xanthomas possess no malignant potential, a follow-up cystoscopy is considered unnecessary.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, these fi ndings may be due to several other malignant and non-malignant differential diagnoses, such as nephrogenic adenoma, inverted papilloma, leiomyoma, amyloidosis, glandular cystitis, endometriosis, bladder xanthoma, among others (3)(4)(5)(6). Cystoscopy is the gold standard procedure to investigate patients with suspicion of any bladder neoplasia.…”
Section: Introductionmentioning
confidence: 99%